Do long-term tongue piercings affect speech quality?. (3rd July 2017) - Heinen, Esther; Birkholz, Peter; Willmes, Klaus; Neuschaefer-Rube, Christiane
Abstract: Purpose: To explore possible effects of tongue piercing on perceived speech quality. Methods : Using a quasi-experimental design, we analyzed the effect of tongue piercing on speech in a perception experiment. Samples of spontaneous speech and read speech were recorded from 20 long-term pierced and 20 non-pierced individuals (10 males, 10 females each). The individuals having a tongue piercing were recorded with attached and removed piercing. The audio samples were blindly rated by 26 female and 20 male laypersons and by 5 female speech-language pathologists with regard to perceived speech quality along 5 dimensions: speech clarity, speech rate, prosody, rhythm and fluency. Results: We found no statistically significant differences for any of the speech quality dimensions between the pierced and non-pierced individuals, neither for the read nor for the spontaneous speech. In addition, neither length nor position of piercing had a significant effect on speech quality. The removal of tongue piercings had no effects on speech performance either. Rating differences between laypersons and speech-language pathologists were not dependent on the presence of a tongue piercing. Conclusions: People are able to perfectly adapt their articulation to long-term tongue piercings such that their speech quality is not perceptually affected.